2020
DOI: 10.18502/ijph.v48i12.3569
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate Combined with Nifedipine Is Effective in Pregnancy-Induced Hypertension and Reduces Levels of Serum β2- Microglobulin and Retinol Binding Protein 4

Abstract: The article's abstract is no available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It was suggested that the combination of nifedipine tablets and magnesium sulfate was effective in improving hypercoagulability in patients with pregnancy-induced hypertension, and was more effective than magnesium sulfate alone. SONG ( 13 ) and others have confirmed that nifedipine combined with magnesium sulfate has a good therapeutic effect on patients with pregnancy-induced hypertension, and the clinical effect is significant.…”
Section: Discussionmentioning
confidence: 89%
“…It was suggested that the combination of nifedipine tablets and magnesium sulfate was effective in improving hypercoagulability in patients with pregnancy-induced hypertension, and was more effective than magnesium sulfate alone. SONG ( 13 ) and others have confirmed that nifedipine combined with magnesium sulfate has a good therapeutic effect on patients with pregnancy-induced hypertension, and the clinical effect is significant.…”
Section: Discussionmentioning
confidence: 89%